2014
DOI: 10.1007/s00702-014-1240-0
|View full text |Cite
|
Sign up to set email alerts
|

Information handling by the brain: proposal of a new “paradigm” involving the roamer type of volume transmission and the tunneling nanotube type of wiring transmission

Abstract: The current view on the organization of the central nervous system (CNS) is basically anchored to the paradigm describing the brain as formed by networks of neurons interconnected by synapses. Synaptic contacts are a fundamental characteristic for describing CNS operations, but increasing evidence accumulated in the last 30 years pointed to a refinement of this view. A possible overcoming of the classical "neuroscience paradigm" will be here outlined, based on the following hypotheses: (1) the basic morpho-fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 144 publications
0
18
0
Order By: Relevance
“…Different types of MV have been described (see Agnati et al, 2014), but two types are of importance for our discussion. Exosomes are vesicles (40-100 nm in diameter) contained in the so-called early, late, or recycling endosomes, a type of multivesicular bodies.…”
Section: Intercellular Transfer By Microvesicles (Mvs)mentioning
confidence: 99%
“…Different types of MV have been described (see Agnati et al, 2014), but two types are of importance for our discussion. Exosomes are vesicles (40-100 nm in diameter) contained in the so-called early, late, or recycling endosomes, a type of multivesicular bodies.…”
Section: Intercellular Transfer By Microvesicles (Mvs)mentioning
confidence: 99%
“…The basic dichotomous classification of intercellular communication in the brain proposed almost three decades ago (Agnati et al, 1986; see also Agnati and Fuxe, 2000) can also easily accommodate recent evidence concerning the existence of other specialized structures for intercellular communication, such as micro-vesicles for a well-demonstrated VT type ) and tunneling nanotubes for a WT that is not yet in vivo demonstrated in the brain (Rustom et al, 2004). Thus, recently a more complete classification has been suggested for both VT and WT (see Agnati et al, 2010aAgnati et al, , 2014. As far as the VT is concerned, the distinction has been proposed between 'classical VT' (migration of chemical and physical signals) and roamer type of VT (RT-VT) (migration of micro-vesicles, see below).…”
Section: Wt and Especially Vt Allow The Assemblage Of Complex Cellulamentioning
confidence: 99%
“…In particular, it has allowed us to introduce the concept of CCNs (Agnati and Fuxe, 2000), i.e., the set of cells of any type, which by exploiting the entire spectrum of intercellular communication modes are capable of integrating multiple inputs to give out appropriate outputs and to support each other's survival (Agnati and Fuxe, 2000;Agnati et al, 2014). It can be surmised that an interplay between astrocytes and neurons occurs in organizing the CCNs especially via astrocytic release of gliotransmitters that are similar to known neurotransmitters and interact with target receptors similar to those targeted by neurotransmitters.…”
Section: Wt and Especially Vt Allow The Assemblage Of Complex Cellulamentioning
confidence: 99%
“…VT is also known as "nonsynaptic diffusion neurotransmission" (Bach-Y-Rita, 1993Kercel, 2004). In a recently published paper, Agnati et al (2014) highlighted that two newly discovered signal transmission types in the brain seem to be of significant importance to further understand the function of the brain: signaling via (i) membrane nanotubes (a new form of WT), and (ii) via extracellular vesicles (a new form of VT). Agnati et al conclude that "their importance in integrative actions is potentially enormous" (Agnati et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In a recently published paper, Agnati et al (2014) highlighted that two newly discovered signal transmission types in the brain seem to be of significant importance to further understand the function of the brain: signaling via (i) membrane nanotubes (a new form of WT), and (ii) via extracellular vesicles (a new form of VT). Agnati et al conclude that "their importance in integrative actions is potentially enormous" (Agnati et al, 2014). In parallel, more and more research is showing that endogenous electromagnetic fields play a fundamental role, and it is concluded that "endogenous brain activity can causally affect neural function through field effects under physiological conditions" (Anastassiou et al, 2011).…”
Section: Introductionmentioning
confidence: 99%